Changes in pontine and preBötzinger/Bötzinger complex neuronal activity during remifentanil-induced respiratory depression in decerebrate dogs - Palkovic, Barbara; Mustapic, Sanda; Saric, Ivana; Stuth, Eckehard A. E.; Stucke, Astrid G.; Zuperku, Edward J. (Frontiers in Physiology, 2023)
In vivo studies using selective, localized opioid antagonist injections or localized opioid receptor deletion have identified that systemic opioids dose-dependently depress respiratory output through effects in multiple respiratory-related brainstem areas. With approval of the subcommittee on animal studies of the Zablocki VA Medical Center, experiments were performed in 53 decerebrate, vagotomized, mechanically ventilated dogs of either sex during isocapnic hyperoxia. We performed single neuron recordings in the Pontine Respiratory Group (PRG, n=432) and preBötzinger/Bötzinger complex region (preBötC/BötC, n=213) before and during intravenous remifentanil infusion (0.1-1mcg/kg/min) and then until complete recovery of phrenic nerve activity. A generalized linear mixed model was used to determine changes in Fn with remifentanil and the statistical association between remifentanil-induced changes in Fn and changes in inspiratory and expiratory duration and peak phrenic activity. Analysis was controlled via random effects for animal, run, and neuron type. Remifentanil decreased Fn in most neuron subtypes in the preBötC/BötC as well as in inspiratory (I), inspiratory-expiratory, expiratory (E) decrementing and non-respiratory modulated neurons in the PRG. The decrease in PRG inspiratory and non-respiratory modulated neuronal activity was associated with an increase in inspiratory duration. In the preBötC, the decrease in I-decrementing neuron activity was associated with an increase in expiratory and of E-decrementing activity with an increase in inspiratory duration. In contrast, decreased activity of I-augmenting neurons was associated with a decrease in inspiratory duration. While statistical associations do not necessarily imply a causal relationship, our data suggest mechanisms for the opioid-induced increase in expiratory duration in the PRG and preBötC/BötC and how inspiratory failure at high opioid doses may result from a decrease in activity and decrease in slope of the pre-inspiratory ramp-like activity in preBötC/BötC pre-inspiratory neurons combined with a depression of preBötC/BötC I-augmenting neurons. Additional studies must clarify whether the observed changes in neuronal activity are due to direct neuronal inhibition or decreased excitatory inputs.